2021
DOI: 10.1186/s12891-021-04599-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome following rotator cuff tear repair in a low-income population. Impact of obesity and smoking

Abstract: Background Comorbidities and socioeconomic issues impact outcome of rotator cuff tear (RCT) repair. There are no data on RCT repair outcome from developing regions. We determined the impact of obesity and smoking following RCT repair in a low-income population. Methods This is a retrospective case series. Forty-seven shoulders of 42 patients subjected to open or arthroscopic repair of a RCT with a minimum of 2 years follow-up were cross-sectionally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Overall, 6 studies reported follow-up pain scores. Out of these, five assessed pain using the visual analogue scale (VAS) [ 17 19 , 25 , 27 ] and one using the PROMIS pain interference scale [ 23 ]. In both these scales, a higher score indicates greater pain intensity [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 6 studies reported follow-up pain scores. Out of these, five assessed pain using the visual analogue scale (VAS) [ 17 19 , 25 , 27 ] and one using the PROMIS pain interference scale [ 23 ]. In both these scales, a higher score indicates greater pain intensity [ 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent comprehensive review of the full texts of the remaining 25 studies resulted in the exclusion of 14 more studies. Finally, we conducted our meta-analysis with data from 11 retrospective studies (Fig 1) [17][18][19][20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the need for RSA, delayed RCT repair is linked to a higher chance of developing RCA. Thus, earlier referral and treatment for RCT might have impacted our results [ 1 ]. We may speculate that adequate timing of RCT repair in our hands could have reduced the need for replacement of the shoulder joint.…”
Section: Discussionmentioning
confidence: 99%
“…Reverse shoulder arthroplasty (RSA) is currently the most commonly employed surgical treatment for rotator cuff arthropathy (RCA), especially among elderly patients. This procedure can also be indicated in patients with irreparable rotator cuff injuries, severe proximal humerus fractures, inflammatory arthropathies as well as for revision of primary arthroplasty being contraindicated when there is severe impairment of the deltoid muscle [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been described that may be determinant in establishing a favorable prognosis in the patient’s recovery after this surgery, including: demographic factors (minority age and male gender), clinical factors (absence of osteoporosis, absence of diabetes, high-performance athlete patient, and complete passive preoperative range of motion), factors related to the integrity of the rotator cuff or to the intervention (repair in the same procedure of the acromioclavicular or biceps joint) [ 1 , 3 , 11 ] and socioeconomic factors [ 12 ]. However, the relationship of diabetes with this pathology and its therapeutic management is not entirely clarified.…”
Section: Introductionmentioning
confidence: 99%